Effect of aging on growth hormone-leptin axis in normal and obese healthy subjects - Razak Al-Sharifi, Zaineb A.; El-Yassin, Hedef D. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Growth hormone is a hormone responsible for the normal body growth and development by stimulation protein production in muscle cells and energy release for breakdown of fat. On the other hand leptin is a newly discovered hormone that is mainly synthesized in adipose tissues it decreases food intake by causing satiety and promoting energy combustion . Both aging and obesity are associated with a reduction in growth hormone secretion. In the mean time obese humans have increased circulating leptin. Objective: The aim of this paper is to shed light on the contribution of these two hormones in the mechanism of aging process in an attempt of improving this process for a better life at old ages. Sera from blood samples were used to carry out certain biochemical parameters and hormone (growth hormone and leptin). Results: The results obtained show a decrease in the level of growth hormone with progression of age. In the mean time there is an increase in the level of serum leptin with the advancement of age. Aging is usually associated with adiposity. Increasing fat with age is probably multifactorial one potential mechanism for that is reduced leptin transport across blood-brain barrier.. Conclusion: The increase in leptin level which was observed in elderly age group and obese group suggest that the associated decrease in growth hormone serum level is related to obesity in general and in particular to the aging process.